DSP for Mobile Wireless LTE System: A Review - Ashwaq Q. Hameed; Salman goli; Mohammed K. shoubith (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Long term evolution (LTE) is the last step towards the 4G of radio technologies designed to increase the capacity and speed of cellular networks. With the appearing of 4G LTE networks, there has been increasing interests and special attention is paid to the performance and power characteristics as compared with 3G networks. This paper provides detailed information about mobile wireless MIMO-LTE system. It is also presents a brief explanation of the characteristics, performance and state of art techniques used within mobile wireless MIMO-LTE system. There are several types of commercial digital signal processing (DSP) chips available in marks which can be used with MIMO- LTE system. Therefore, this work will be focuses on the applications of commercial DSPs in MIMO-LTE system and taking into consideration types and characteristics where can enables efficient baseband processing for 3G,4G and MIMO-LTE wireless system equipment with its scalable, highperformance architecture.